ANALISIS KESULITAN BELAJAR SISWA KELAS V PADA MATERI PERKALIAN DALAM PEMBELAJARAN MATEMATIKA DI SDI NAIKOTEN 1 - Herolima Lasa Kelen; Febe Priskila Tefa; Lili Missa; Maria Januaria Meo Mesa; Adam Bol Nifu Benu; Habibi Musa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify the learning difficulties experienced by fifth-grade students in understanding multiplication at SDI Naikoten 1. The research used a descriptive quantitative approach with 24 students as participants. Data were gathered through questionnaires, classroom observations, and students' written work. A 15-item Likert scale questionnaire was used to measure their level of difficulty. The results show that the average score was 2.61, which falls into the